Transitions in informal apprenticeship : results from ILO research in several African countries - Hofmann, Christine [Verfasser]; Okolo, Wendy [Verfasser] (My University, 2013)
"Informal apprenticeship is a major route for African youth to gain employable skills and enter the labour market. Transitions in informal apprenticeship are discussed in terms of access to apprenticeships, dropout rates, and transitions to the world of work upon completion. Building on studies conducted in several African countries, this paper concludes that, while each of these countries is diverse in their settings, transitions in informal apprenticeship remain entrenched in local tradition and practices. Transitions to formal sector jobs are possible, but only for a lucky few." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.3.1 Afrika; Informeller Sektor; Berufsausbildung; Berufseinmündung; Erste Schwelle; Zweite Schwelle; Bildungschancengleichheit; Afrika